Outcomes of Antiretroviral Therapy in Pediatric HIV - infected Patients in Phra Nakhon Si Ayutthaya Hospital - Krongapiradee, Sutin (Journal of Health Science of Thailand, 2018)
Highly active antiretroviral therapy (HAART) has been introduced into pediatric HIV - infected patients treatment regimen since March 2004. A retrospective analytic study was done to determine background data and outcomes from March 2004 to February 2008, and included a total of 25 enrolled cases, of which 56 percent were male. Mean ages at the time of diagnosis and initial treatment were 4.83, SD 3.92 and 5.54, SD 3.85 years respectively. Most of the cases were born from HIV- infected mother and most of the caretakers were within the families. Sixty percent of the cases were classified as clinical category C. Ninety six percent acquired opportunistic infections such as tuberculosis, Pneumocystis carinii pneumonia and Candidiasis. Almost all of the cases received 3TC+ d4T+NVP regimen except one sensitive case required 3TC+ d4T+EFV regimen. The outcomes showed a positive trend of clinical and immunological improvement with statistical significance (p < 0.05), at the most. Resistance to the first line drug regimen was observed.